The application of system usability scale method to measure the usability of electronic learning system (e-learning) of politeknik caltex riau - Sari, Rika Perdana; Henim, Silvana Rasio (ILKOM Jurnal Ilmiah, 2021)
The COVID-19 disaster, which was felt globally in all countries including Indonesia, has in general changed the series of business process arrangements in almost all fields, including the field of education. One of the affected areas of education is the Caltex Riau Polytechnic (PCR) campus. The impact of this disaster has forced the academic community (lecturers and students) to carry out the online lecture process since the Odd semester of the 2020/2021 academic year. The online lecture process is facilitated by an electronic learning system (e-learning). Changes in the pattern of lectures, which previously were held face-to-face, then had to be conducted online using e-learning, gave rise to several usability problems. The usability measurement of e-learning PCR was carried out using the System Usability Scale (SUS) questionnaire, involving 196 participants. The results of the usability analysis of e-learning PCR obtained a score of 58.75. With the assessment criteria on the adjective, the rating is okay, the grade scale is D value, and the acceptable ranges are at a marginal low. This means that e-learning still needs improvement and evaluation of the utilization of the features/services provided, so that it can be used more efficiently, effectively, and satisfactorily for its users.